2022
DOI: 10.3390/ijerph19073945
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Substances Associated with Chronic Obstructive Pulmonary Disease—A Scoping Review

Abstract: Chronic obstructive pulmonary disease (COPD) is a slowly developing non-communicable disease (NCD), causing non-reversible obstruction and leading to marked morbidity and mortality. Besides traditional risk factors such as smoking, some environmental substances can augment the risk of COPD. The European Human Biomonitoring Initiative (HBM4EU) is a program evaluating citizens’ exposure to various environmental substances and their possible health impacts. Within the HBM4EU, eighteen priority substances or subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…A study on the relationship between occupational exposure and the clinical features of COPD showed that those with COPD reported more symptoms associated with occupational exposure, even if they had a history of smoking [ 40 ]. The European Human Biomonitoring Initiative (HBM4EU) review of the scope of COPD and environmental substances reported that exposure to Pb was associated with COPD, while Cd, Cr, and As may be associated with COPD and/or decreased lung function [ 41 ]. In this study, we did not determine which specific metals may lead to an increased risk of COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on the relationship between occupational exposure and the clinical features of COPD showed that those with COPD reported more symptoms associated with occupational exposure, even if they had a history of smoking [ 40 ]. The European Human Biomonitoring Initiative (HBM4EU) review of the scope of COPD and environmental substances reported that exposure to Pb was associated with COPD, while Cd, Cr, and As may be associated with COPD and/or decreased lung function [ 41 ]. In this study, we did not determine which specific metals may lead to an increased risk of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…At present, patients with COPD are not exposed to one single substance in the environment, and it is particularly important to study the interaction between exposed substances [ 41 ]. Boggia et al confirmed a significant interaction ( p < 0.001) between smoking and occupational exposure on the risk of COPD and increased risk among workers exposed to both risk factors (ExpB:2.51) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…PM10 can penetrate deeper into the lungs, targeting the lung bronchioles and resulting in remodeling of lung tissue and the upregulation of immune cells [140]. Damage to lung architecture and altered immune response elevate the likelihood of lung diseases such as chronic obstructive pulmonary disease (COPD), chronic bronchitis, and respiratory tract infections due to resulting lung impairment and dysfunction post-exposure to environmental toxins [43,141,142].…”
Section: Environmental Toxins and Immune Response In The Lungsmentioning
confidence: 99%
“…The mechanisms implicated in the induction or exacerbation of airway inflammatory responses by PAHs were studied over the years, while several are described in some review studies. When fine particles like PAHs are breathed into the lungs, they cause inflammation, which is one of the mechanisms implicated in the development, and also the exacerbation, of many respiratory diseases [ 11 ]. Research in the field of pollution is focused mostly on the urban environment [ 12 ] because it was found that most of the pollution is transmitted from outside to inside, while smoking and cooking contribute to internal pollution in a relatively stable interval [ 12 ].…”
Section: Introductionmentioning
confidence: 99%